Anthelmintic Potential Extract Mango Gadung Seed (Mangifera indica L.) Mecistocirrus digitatus in vitro - Ria Nikmatul Jannah; Sri Mumpuni Sosiawati; Sri Chusniati; Kusnoto Kusnoto; Rahmi Sugihartuti; Setiawati Sigit (Journal of Parasite Science (JoPS), 2017)
This research aim to attest the potential anthelmintic extract  mango seed gadung  (Mangifera indica L.) against worms Mecistosirrus digitatus in vitro, the study also aims to determine the effect of immersion time, variasis concentration and the relationship between time and treatment. this study used 210 M. digitatus worm extracted regardless of gender worms. treatment that is given was  the concentration  extract  mango seed gadung  was 5%, 7.07%, 10%, 14.14%, 20%, negative control using NaCl physiological  and comparison using levamisole Hidrokloride 0.0025 mL. Observations death worm Mecistocirrus digitatus and observations were made at the 6th hour, 12th hour, 18th hour and 24th hour. The results showed that variations in concentration, soaking time and the relationship between soaking time with the treatment affect mortality Mecistocirrus digitatus worms. Test results of the analysis statitistik using factorial Anova and Duncan's Multiple Range Test showed a significant difference (p<0.01) between the time factor, variations in concentration and relations between time and treatment.